The Effect of Simulation-Based Education on Youth Preparedness in Facing the Gamalama Volcano Eruption Disaster in Tobololo Village - Aminudin Muhammad; Fitriyanti N Idrus (Jurnal Kesehatan, 2024)
A natural disaster is an event caused by nature that can occur at any time, one of which is a volcanic eruption. Understanding of disaster preparedness needs to be understood by all levels of society to reduce various impacts, both material and non-material, caused by the threat of volcanic disasters. One of the communities that play a role in disaster management is the youth. Youth can play a role in knowledge and attitudes about disasters. Therefore, efforts can be made to improve preparedness in reducing disaster risk through simulation-based education. Purpose: This study aims to analyze the effect of disaster simulation education on the level of youth preparedness to face the eruption of the Gamalama volcano in Ternate Village, Tobololo Ternate. Methods: This study uses a quasi-experimental one-group pretest-posttest design. Results: the study showed that the majority (30.2%) of respondents received a preparedness score of 50 prior to disaster simulation-based education. The value of preparedness after conducting education based on disaster simulation, the majority (76.7%) of respondents got a value of 85.90. The results of the T-test statistic with (ɑ = 0.05) obtained a p-value of 0.000 which means that there is an effect of education based on disaster simulation on preparedness facing a volcanic eruption disaster in Youth in Tobololo Village, West Ternate City District Conclusion: Disaster simulation-based education affects youth preparedness in dealing with volcanic eruptions